Die religieus-kulturele leefwyse as uitgangspunt vir onderwysbeplanning - Steyn, Jeannette (Koers, 1988)
The discussion in this article centres on the hypothesis that the religious and cultural way of life, based upon the fundamental principle of universality and individuality, should be the point of departure in any type of educational planning. The bases of two education acts are discussed in the light of historical facts and the viewpoints of several authors, and considered in the perspective of the fundamental principle of universality and individuality.